Advances in Transition-Metal-Catalyzed Direct sp3-Carbon–Hydrogen Bond Functionalization - Zhang, Wei; Wang, Nai-Xing; Xing, Yalan (Synlett, 2015)
Transition-metal-catalyzed direct carbon–hydrogen bond functionalization has made significant advances in the field of carbon–hydrogen bond activation over the past decades. This methodology has the potential to be used in many different areas of chemistry; for example, it can provide an opportunity for the synthesis of various kinds of complex compounds. This account mainly focuses on recent advances in transition-metal-catalyzed direct sp3-carbon–hydrogen bond functionalization to form carbon–carbon bonds.1 Introduction2 Carbon–Carbon Bond Formation via Direct sp3-Carbon–Hydrogen Bond Functionalization2.1 Coupling of sp3-Carbon–Hydrogen and sp-Carbon–Hydrogen Bonds2.2 Coupling of sp3-Carbon–Hydrogen and sp2-Carbon–Hydrogen Bonds2.3 Coupling of sp3-Carbon–Hydrogen and sp3-Carbon–Hydrogen Bonds2.4 Coupling of sp3-Carbon–Hydrogen and C–X Bonds3 Conclusion
Keywords: transition metals; catalysis; carbon–carbon bond formations; cross-dehydrogenative coupling; direct bond functionalizations